VISIBILITAS HUBUNGAN KEMITRAAN PADA POLA INTERAKSI SUAMI-ISTRI DALAM PANDANGAN AL-SYAFI’I - Qadafy, Mu’ammar Zayn (Sunan Kalijaga State Islamic University & The Asia Foundation, 2015)
The Perspective of al-Syafi’I on Partnership in Marriage In husband and wife relationships, contemporary couples prefer a partnership pattern rather than one of leadership. Although the latter is not necessary better than the former, it is obviously more accommodative of modern ideas of justice, egalitarianism and gender equality. This article aims to explore the connections between household partnership patterns, as fundamental to contemporary Muslim’s, and the traditional Islamic jurisprudence (fikih) most dominant among the diverse adherents of Islam. More specifically, this research describes al-Syafi`í thought. To explore the partnership patterns of married couples, it elaborates on three points: (1) the meaning of qawwamuna, (2) the concept of bride price and household expenses, and (3) interactions between husband and wife. The primary resource use in this research is al-Umm. This article concludes that Syafi’i jurisprudence implicitly accommodates the idea of partnership between marriage partners, as evident in (1) the acknowledgement of a woman’s right to choose her husband; (2) the bride price, which has both legal, formal and moral implications; (3) the co-understanding of the marriage partners in matters of household expenses and the emphasizing of discussion in solving financial problems; and (4) the use of good reason in dealing with household and personal conflicts.